Preservation of fertility in teenagers and young adults treated for haematological malignancies. Issue 2 (February 2021) - Yasmin, Ephia; Mitchell, Rod; Lane, Sheila
Summary: As survival rates in teenagers and young adults diagnosed with haematological malignancies now exceed 70%, it is important that long-term quality of life, including measures to protect future fertility, are considered and discussed with patients and their families. Although discussion on the effect of planned cancer treatment on fertility is standard of care, knowledge of potential fertility treatment options and when they should be offered in haematological malignancies is not always so clear. In each case, the advice on the appropriate preservation of fertility depends upon a complex interplay of factors, weighing out the risk of future infertility against the risk of fertility preservation treatment, and recommendations must be made on a case-by-case basis. The aim of this Review is to evaluate the gonadotoxicity of treatments of prevalent haematological malignancies in teenagers and young adults, and provide an evidence-based framework to help with fertility discussion and management at the time of diagnosis, relapse or resistant disease, and in long-term follow-up settings.